Efficacy and safety of SH003 on immune function: study protocol for a randomized, double-blind placebo-controlled clinical trial - Chunhoo Cheon; Seong-Gyu Ko (BMC Complementary Medicine and Therapies)
Abstract Background The immune system is essential for defending the body against pathogens and maintaining homeostasis. Recent global public health challenges have increased interest in natural products that enhance immune function. SH003, a compound derived from Astragalus membranaceus, Angelica gigas Radix, and Trichosanthis Radix, has shown potential as an immunomodulatory agent. This study aims to evaluate the efficacy and safety of SH003 in improving immune function in individuals with a mildly weakened immune systems. Methods This randomized, double-blind, placebo-controlled trial will be conducted over 8 weeks with 120 participants aged 19 to 75 years who have experienced two or more upper respiratory infections in the past year. Participants will be randomly assigned to receive either SH003 or a placebo. The primary outcome is the change in natural killer cell activity. Secondary outcomes include cytokines levels (IL-2, IL-12, IFN-γ, TNF-α), inflammation markers (CRP, ESR), and stress and respiratory symptoms. Safety outcomes will be monitored through vital signs and laboratory tests. Discussion This study represents the first clinical trial to evaluate the immune-enhancing effects of SH003 in a general population with mild immune system impairment. The results could offer valuable insights into the potential of SH003 as a novel immune support intervention. Trial registration Clinical Research Information Service (registration number: KCT0009424, May 10, 2024, https://cris.nih.go.kr ). Retrospectively registered.